Leadership styles influence employee’s turnover intention / Nur Nadia Nattasha Che Ahmad and Nadiah A. Manaf - Che Ahmad, Nur Nadia Nattasha; A. Manaf, Nadiah (Faculty of Business and Management, 2014)
The main purpose of conducting this study is to investigate either leadership styles influence employee’s turnover intention. KSL Resorts at Johor Bahru has been chosen as the location for pursuing this study. The full range of leadership styles which are transformational, transactional, and laissez faire represented as the independent variable. Meanwhile, the dependent variable for this study is employee’s turnover intention. In order to gather the data, 113 sets of questionnaire have been distributed to the respondents who are being chosen among KSL Resorts’ employees. The data obtained is be analyzed by Statistical Package for Social Science Version 21 (SPSSv21). The result is successfully answered the objectives which is all of the three leadership style are positively influence turnover intention. In addition, the most dominant leadership style that influence employee’s turnover intention in KSL Resorts is transformational leadership style.